Dissemination and promotion of cultural heritage and ICT tools – the interaction between law and economy - Jagielska-Burduk, Alicja (The Opole Studies in Administration and Law, 2016)
This paper deals with legal and economic considerations dissemination and promotion of cultural heritage. The aim of the paper was to analyse if the existing national strategy concerning cultural heritage protection accepts the use of new technologies in cultural heritage management and education of society.